Future tech : innovations in transportation. - Schilperoord, Paul, ....- (London : Black Dog, 2006)
From Leonardo da Vinci's fantastic visions, to Richard Branson's plans to offer commercial space travel by 2010, visionaries and entrepreneurs have long dreamed of how we will travel in the future. "Future Tech: Innovations in Transportation" is a prescient look at how we will be moving forward over the coming decades. Whilst we are not yet travelling to work using jet-powered backpacks, the issue of transport in the future is becoming increasingly important. As roads have become more congested and the environment more fragile, the means of transport at our disposal seem less and less adequate. "Future Tech" explores what designers and engineers around the globe are developing for the world of tomorrow. "Future Tech" features prototypes already in the first stages of manufacture alongside more conceptual, speculative designs, as well as a history of mechanised transport and invention through the ages. There are chapters on public transport, road, air and water travel as well as personal mobility. With further information on sustainable fuels, gravity, solar and wind power alongside other fascinating projects, "Future Tech" is truly a compelling exploration of how the future is imagined in the present.
Keywords: Voertuigen